Perioperative Management of Pheochromocytoma/Paraganglioma: Is There a State of the Art? - Mannelli, M.; Dralle, H.; Lenders, J.W. M. (Hormone and Metabolic Research, 2012)
Pheochromocytoma and paraganglioma are rare tumors of sympathetic or parasympathetic origin, presenting with a highly variable clinical picture. Rarity, as well as biological, clinical, and genetic heterogeneity are barriers to initiate prospective studies that help to establish clinical guidelines. The best management of these patients relies on the experience of a multidisciplinary team. The ultimate outcome can benefit from adequate pre-surgical evaluation and treatment as well as an accurate post-surgical follow-up. Long-term follow-up is mandatory in all patients, but is particularly important in specific familial cases such as those with an SDHB mutation where the risks of recurrence are higher. The surgical approach varies depending on tumor size, location, and surgeon’s personal attitude and experience. In this paper, we summarize recommendations, based mostly on authors’ and other experts’ personal experiences, for the best possible management of patients prior, during and after surgery, as well as when pheochromocytoma is diagnosed during pregnancy.
Keywords: pheochromocytoma; anesthesia; surgery; pregnancy